Human Brain versus Artificial Intelligence: A Physiological Perspective on Cognition, Learning and Information Processing - Ajit Pahari; Sanjit Kumar Kar; Bishal Joshi; Riya Ghosh (Journal of Universal College of Medical Sciences, 2025)
INTRODUCTION Artificial intelligence (AI) is an interdisciplinary field of computer science, integrating insights from various fields including mathematics, neurophysiology, psychology, linguistics and philosophy. AI’s primary goal is to mimic some aspects of human cognition, such as pattern recognition, judgment, and even original problem-solving. MATERIAL AND METHODS In this article review and analysis of the available literature was dove. Literature was searched from Google Scholar, ScienceDirect and PubMed using keywords Artificial Intelligence, Human Intelligence, Human Al collaboration and neuroplasticity. RESULTS This conceptual review found that human brain and the artificial intelligence have different capabilities. The brain is powerful because of its creativity, cognitive flexibility, inherent awareness, and ethical reasoning, whereas AI is powerful because of its incredible speed, data processing precision, and scalability. Because of this, they are not rivals but ideal partners, and their synergistic collaboration is the demand of future. CONCLUSION With their distinct capabilities, human brain and AI should complement each other. This collaboration will allow us to combine the deep holistic understanding and ethical reasoning of humans with the computational power and data-processing capabilities of machines.